The Phenomenon of Dividend Announcement on Stock Abnormal Return (Case in ASEAN Countries) - Hariyanto, Ikka Tiaraintan; Murhadi, Werner Ria (Jurnal Manajemen Bisnis, 2021)
Research aims: to examine the existence of stock’s abnormal return after dividend announcement activity.Design/methodology/approach: event study with 1.330 samples of dividend announcement in ASEAN countries during 2018. The research period was 21 days around the dividend announcement’s date.Research findings: this analysis's results agreed with the dividend signaling theory hypotheses, where the increase, decrease, or constant dividends could be an informative aspect for investors. Theoritical contribution/originality: it was shown by the presence of a positive abnormal return between an increase and a constant dividend, while a negative abnormal return between decrease dividends.Practitioner/policy implication: in the ASEAN capital market, it could be concluded that the change of dividend nominal would signal the firm’s prospect.Research limitation/implication: this research used the earliest dividend announcement before revision. Suggestions for further research are to pay attention to announcements of changes in dividend distribution dates and nominal revision, whether they contain information for investors, which will affect stock price movements.